Possible ways to improve the efficiency of mental health care - A. V. Masyakin; G. P. Kostyuk (Неврология, нейропсихиатрия, психосоматика, 2018)
The paper highlights the main ways to increase the efficiency of mental health care according to the data available in foreign and Russian literature. It sets forth the main directions for development of mental health care and the possibilities of their implementation. The basic documents of the World Health Organization, which define the most important vectors of the development of European psychiatry, are considered.